Australia's next-generation Autonomous Underwater Vehicle for Antarctic research - Guihen, D; Zurcher, K; Bowden-Floyd, I; King, P; Lucieer, V (., 2016)
The Antarctic Gateway Partnership has been funded to advance the Australian capacity toundertake Antarctic science and is both improving the understanding of the physical andecological environment and is building the facilities for the next-generation of Antarcticresearch. A crucial component of the Partnership is the development of a high specification,multi-sensor polar Autonomous Underwater Vehicle. A key finding ofSCARs recent Horizon Scanning exercise was the prominent role that AutonomousUnderwater Vehicles (AUV) will play in answering the big questions facing Antarcticscience. These big questions, including the mechanics of sea-ice formation, water columnprocesses and ecosystem dynamics, drive the engineering and scientific focus of theAUVs development. Multiple sensor suites, such as a current profiler, side-scan sonarand hyper-spectral camera will complement the collection of physical samples using asediment corer and a water sampler. Making manifold, simultaneous and diverseobservations from a platform that can travel through the water column, to the seabed orunder ice has the potential to support a wide array of important multidisciplinaryAntarctic research. We will present our vision for this new facility along with an update on its developmentand will lay out the deployment options for the vehicle and how it will enable researchersto investigate processes that have to date been too difficult to access or to sample overwide temporal and spatial scales. We will discuss sensor readiness, future missions andthe benefit that the international community can gain from Australias next-generationpolar AUV.